AN ANALYSIS ON STUDENT’S ERROR OF PASSIVE VOICE IN THE SIMPLE PRESENT - Dede Irawan (Universitas Wiralodra, 2019)
This research is aimed to analyze and to know an error of the passive voice in the simple present, passive is needed in daily speaking and writing activity. In this research, the writers use a qualitative method and took 25 students as a sample of this research. While the result of this research, among others: 1. there are 5 students who error on the use of verb, the students are looked confused to choose between Verb 2 and Also Verb 3 (Past Participle), the student cannot distinguish between irregular verb, regular verb and Verb 3 (Past Participle), 2. 4 students’ error on the use to be they can distinguish to be in the passive voice with the use to be in past tense, 3. 6 students’ error in the use to be and verb on passive voice of simple present. Penelitian ini bertujuan untuk menganalisis dan mengetahui kesalahan passive voice pada simple present, passive voice sangat dibutuhkan dalam kegiatan berbicara dan menulis sehari-hari. Dalam penelitian ini penulis menggunakan metode kualitatif dan mengambil 25 siswa sebagai sampel penelitian. Adapun Hasil penelitian ini antara lain: 1. ada 5 siswa yang melakukan kesalahan dalam penggunaan kata kerja, siswa terlihat bingung untuk memilih antara kata kerja 2 dan kata kerja 3 (Past Participle), siswa tidak dapat membedakan antara kata kerja tidak teratur, kata kerja reguler dan Kata kerja 3 (Past Participle), 2. Ada 4 siswa yang melakukan kesalahan dalam menggunakan to be, para siswa tidak dapat membedakan to be passive voice dan past tense 3. Ada 6 siswa yang salah dalam penggunaan menjadi dan kata kerja pada passive voice.